Linear algebra: - Poole, David (Thomson/Brooks Cole, 2006)
The Book provides detailed and complete solutions to the odd-numbered exercises and test questions; section and chapter summaries of symbols, definitions, and theorems; study tips and hints. Complex exercises are explored through a question-and-answer format designed to deepen understanding. Challenging and entertaining problems that further explore selected exercises are also included